Cancer cell-autonomous overactivation of PARP1 compromises immunosurveillance in non-small cell lung cancer. Issue 6 (30th June 2022) - Juncheng, Pan; Joseph, Adrien; Lafarge, Antoine; Martins, Isabelle; Obrist, Florine; Pol, Jonathan; Saavedra, Ester; Li, Sijing; Sauvat, Allan; Cerrato, Giulia; Lévesque, Sarah; Leduc, Marion; et al.
Abstract : Background: High activity of poly(ADP-ribose) polymerase-1 (PARP1) in non-small cell lung cancer (NSCLC) cells leads to an increase in immunohistochemically detectable PAR, correlating with poor prognosis in patients with NSCLC, as well as reduced tumor infiltration by cytotoxic T lymphocytes (CTLs). Intrigued by this observation, we decided to determine whether PARP1 activity in NSCLC cells may cause an alteration of anticancer immunosurveillance. Methods: Continuous culture of mouse NSCLC cells in the presence of cisplatin led to the generation of cisplatin-resistant PAR high clones. As compared with their parental controls, such PAR high cells formed tumors that were less infiltrated by CTLs when they were injected into immunocompetent mice, suggesting a causative link between high PARP1 activity and compromised immunosurveillance. To confirm this cause-and-effect relationship, we used CRISPR/Cas9 technology to knock out PARP1 in two PAR high NSCLC mouse cell lines (Lewis lung cancer [LLC] and tissue culture number one [TC1]), showing that the removal of PARP1 indeed restored cisplatin-induced cell death responses. Results: PARP1 knockout (PARP1 KO ) cells became largely resistant to the PARP inhibitor niraparib, meaning that they exhibited less cell death induction, reduced DNA damage response, attenuated metabolic shifts and no induction of PD-L1 and MHC class-I molecules that may affect their immunogenicity. PAR high tumors implanted in mice responded to niraparib irrespective of the presence or absence of T lymphocytes, suggesting that cancer cell-autonomous effects of niraparib dominate over its possible immunomodulatory action. While PAR high NSCLC mouse cell lines proliferated similarly in immunocompetent and T cell-deficient mice, PARP1 KO cells were strongly affected by the presence of T cells. PARP1 KO LLC tumors grew more quickly in immunodeficient than in immunocompetent mice, and PARP1 KO TC1 cells could only form tumors in T cell-deficient mice, not in immunocompetent controls. Importantly, as compared with PAR high controls, the PARP1 KO LLC tumors exhibited signs of T cell activation in the immune infiltrate such as higher inducible costimulator (ICOS) expression and lower PD-1 expression on CTLs. Conclusions: These results prove at the genetic level that PARP1 activity within malignant cells modulates the tumor microenvironment.